The degree to which educational supervisors possess the ethics of the profession from the teachers' point of view in the Hebron governorate - Abu Khayran, Ashraf Mohammad; Alswaiti, Eman Mousa; Al-Qassim, Hussam hussni (Journal of Educational and Psychological Sciences, 2021)
This study aimed to investigate the degree to which educational supervisors possess professional ethics from the teachers ’point of view in the Hebron Governorate. This study was conducted on all school teachers in the Hebron governorates in the second semester of the academic year 2020/2021 on a sample consisting of (505) teachers. The researcher used the descriptive approach, where by the researcher built the study tool, which relates to the degree of educational supervisors ’ownership of professional ethics from the teachers’ point of view in the Hebron governorate. The researcher made sure of the validity and reliability of the tool.The study found that the degree to which educational supervisors possessed professional ethics from the teachers ’point of view in the Hebron governorate came to a large extent, and there were differences in the degree to which educational supervisors possessed professional ethics from the teachers’ viewpoint in the Hebron governorate depending on the gender variable and in favor of males, and according to the educational qualification variable and in favor of the academic qualification. Master's degree or higher, according to the variable of years of experience and in favor of years of experience (5-10) years, and according to the variable of the teacher’s teaching phase and for the kindergarten phase, and according to the directorate’s variable and in favor of the Yatta district Based on the results of the study, the researcher recommended: Paying attention to the educational supervision process at all levels and fields, giving value to the supervisor's report by granting incentives to teachers, increasing the number of supervisors in all directorates, and increasing the number of supervisors' visits to teachers.
Keywords: Ethics of the Profession; Educational Supervisors; Hebron governorate